A review of the therapeutic management of ulcerative colitis. (November 2022) - Aslam, Nasar; Lo, Sheng Wei; Sikafi, Rafid; Barnes, Tom; Segal, Jonathan; Smith, Philip J; Limdi, Jimmy K
Ulcerative colitis (UC) is a chronic relapsing and remitting gastrointestinal disorder of uncertain aetiology. The last two decades have seen an expansion in the therapeutic arsenal used to treat UC. This has resulted in improved clinical remission and response rates. Nonetheless, staples in our current medical management originate from trials conducted in the early 20th century. In this review article, we aim to outline the key milestones in the history of the medical management of UC in addition to highlighting promising therapeutic developments for the future.